Perancangan Sistem Akuntansi Kas dan Aset Tetap Berbasis Microsoft Excel pada Pura Agung Tirta Bhuana - Made Wedakrisna Mahendradatta; Hafifah Nasution; Ellis Annisa (International Forum of Researchers and Lecturers, 2026)
Pura Agung Tirta Bhuana Bekasi is a nonprofit religious entity that manages cash receipts, cash disbursements, and fixed assets to support worship, social, and community activities. Its administration was previously characterized by simple cash records, nonstandard transaction evidence, time-consuming data retrieval, and incomplete fixed-asset documentation. This study aimed to design a Microsoft Excel-based cash accounting and fixed-asset control system that is orderly, practical, and accountable. The research employed a Research and Development approach using the Waterfall model, comprising requirements analysis, design, implementation, testing, and product finalization. Requirements were identified through observation, interviews, document review, and PIECES analysis. The resulting product consists of two integrated workbooks: a Temple Cash Book and a Fixed Asset Register, accompanied by user manuals. The system automatically generates transaction numbers and asset codes, validates input, produces receipts and payment vouchers, calculates cash balances and straight-line depreciation, and presents cash and asset recapitulations. Black-box testing showed that all seven major functional scenarios operated successfully. The system therefore provides a feasible administrative instrument for improving data traceability, processing efficiency, internal control, transparency, and accountability in temple financial and asset management.